An Integrated Quality Assurance System in Technical, Vocational Education and Training in Nepal (Journal of Technical and Vocational Education and Training, 2021)
A quality assurance system in TVET provides the framework and processes for the consistent delivery of graduates with valid skills and competencies needed in the labor market. It also includes constant review and improvement cycles so the institutions become more efficient and effective in meeting the changing demand of the labour market. Setting and monitoring improvement targets within the system, and then evaluating the quality benefits of those improvements, are key elements of the overall management of the TVET system and as such need to include a variety of relevant measures that are polled consistently according to defined schedules. In this way, quality assuarance system in TVET ensures the effectiveness of system inputs (policy, management systems and processes, infrastructure, human resources, financial resources) to produce the desired outcomes that can be monitored and evaluated to examine if TVET institutions under evaluation responds to labor market, societal and individual needs; leads to nationally, or even internationally, recognized qualifications or credentials; provides access to decent jobs and sustainable employment; is attractive, inclusive and accessible, i.e. all citizens have access to TVET; and fosters capabilities that enable progression to further learning. In this paper, an integrated system of quality assurance is proposed to streamline Nepal's TVET and assure the quality of all institutions delivering TVET in Nepal.